The Educational Quality Assurance System of schools in Chile and its theories of action. A philosophical interrogation (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2021)
The article critically interrogates policy about Quality Assurance and Evaluation of the Chilean school system, focusing on their underlying theories of action from some arguments from Hobbes and Spinoza's political philosophy. In the first part, I describe the educational quality assurance system of the Chilean schools as an example of accountability with high consequences. Subsequently, following Hobbes' approaches, I characterize the theory of action that underlies this quality assurance system from the fear of the sanctions that can be applied to schools in case of a negative performance. On the other hand, I develop an alternative approach to this theory of action that is found in Spinoza's philosophy: there the theory of action highlights the advantage of collaborating in the construction of social life and therefore of the educational task as well. From the intersection of these analyzes, I will show how in the Chilean quality assurance system, both theories of action coexist, generating a theoretical-practical knot that stresses the confidence of the school system. However, I will argue that the role of collaboration between institutional actors of the school system should be strengthened and fear should be abandoned as a mobilizing element of educational quality.Keywords: Accountability. Quality Assurance. Educational policies. Political Philosophy and education.